Determinants of financial performance the case of companies from the former Yugoslavia region - Đaković, Miloš; Andrašić, Jelena; Lalić, Srđan; Kalaš, Branimir; Lukić, Velimir; Ristić Cakić, Milica (Anali Ekonomskog fakulteta u Subotici, 2025)
Profitability is one of the most critical performance indicators of a company and at the same time a very important indicator of importance to the rest of the key business indicators. The aim of this study is to examine the effects of key indicators on the level of profitability of selected companies. The study uses fixed and random effects models as well as a generalized least squares model to analyze panel data of 78 companies from various sectors of the economy, listed on the stock exchanges of former Yugoslavia. The empirical analysis covers the period from 2006 to 2022 and includes indicators of capital structure, liquidity, activity, size, and age of companies. The main results indicate a statistically significant effect of indicators of capital structure and activity, while indicators of age and size also displayed significant effects. The results help enrich the existing literature and refine the knowledge of financial managers in the region for a better understanding of the effects of specific indicators on company performance. The main limitations are the use of only microeconomic indicators in relation to the use of macroeconomic indicators, as well as the analysis of only the ex-Yu region.